Optimalisasi Efisiensi Energi Melalui Perapihan, Gambar Dan Perbaikan Instalasi Listrik Di Ruang Kelas Lantai 1 - Sunardi; Woro Agus Nurtiyanto; Rifa`i Harahap (CV. Multi Kreasi Media, 2024)
In Industry 4.0 which is currently developing, it is very easy for us to create concept designs through calculations using software and also simulations using application software for computer programs, and we as Electrical Engineering Students at Pamulang University want to implement the Tri Dharma of Higher Education, one of which is carrying out community service by theme: